Insect NMDA receptors mediate juvenile hormone biosynthesis - Chiang, Ann-Shyn (The National Academy of Sciences, 2002)
In vertebrates, the N-methyl-d-aspartate subtype of glutamate receptors (NMDAR) appears to play a role in neuronal development, synaptic plasticity, memory formation, and pituitary activity. However, functional NMDAR have not yet been characterized in insects. We have now demonstrated immunohistochemically glutamatergic nerve terminals in the corpora allata of an adult female cockroach, Diploptera punctata. Cockroach corpus allatum (CA) cells, exposed to NMDA in vitro, exhibited elevated cytosolic [Ca(2+)], but not in culture medium nominally free of calcium or containing NMDAR-specific channel blockers: MK-801 and Mg(2+). Sensitivity of cockroach corpora allata to NMDA changed cyclically during the ovarian cycle. Highly active glands of 4-day-old mated females, exposed to 3 μM NMDA, produced 70% more juvenile hormone (JH) in vitro, but the relatively inactive glands of 8-day-old mated females showed little response to the agonist. The stimulatory effect of NMDA was eliminated by augmenting the culture medium with MK-801, conantokin, or high Mg(2+). Having obtained substantive evidence of functioning NMDAR in insect corpora allata, we used reverse transcription PCR to demonstrate two mRNA transcripts, DNMDAR1 and DNMDAR2, in the ring gland and brain of last-instar Drosophila melanogaster. Immunohistochemical labeling, using mouse monoclonal antibody against rat NMDAR1, showed that only one of the three types of endocrine cells in the ring gland, CA cells, expressed rat NMDAR1-like immunoreactive protein. This antibody also labeled two brain neurons in the lateral protocerebrum, one neuron per brain hemisphere. Finally, we used the same primers for DNMDAR1 to demonstrate a fragment of putative NMDA receptor in the corpora allata of Diploptera punctata. Our results suggest that the NMDAR has a role in regulating JH synthesis and that ionotropic-subtype glutamate receptors became specialized early in animal evolution.